2003
DOI: 10.1007/s00023-003-0928-8
|View full text |Cite
|
Sign up to set email alerts
|

Conformal Invariance in Percolation, Self-Avoiding Walks, and Related Problems

Abstract: Over the years, problems like percolation and self-avoiding walks have provided important testing grounds for our understanding of the nature of the critical state. I describe some very recent ideas, as well as some older ones, which cast light both on these problems themselves and on the quantum field theories to which they correspond. These ideas come from conformal field theory, Coulomb gas mappings, and stochastic Loewner evolution.This talk is about 'geometric' critical phenomena. These are random spatial… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 12 publications
(16 reference statements)
0
25
0
Order By: Relevance
“…Also, in the spirit of the conclusion of Cardy's review paper [10] and as already confirmed by [3], the rigorous SLE approach should hopefully become useful and exploited within the theoretical physics community.…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…Also, in the spirit of the conclusion of Cardy's review paper [10] and as already confirmed by [3], the rigorous SLE approach should hopefully become useful and exploited within the theoretical physics community.…”
Section: Introductionmentioning
confidence: 76%
“…It is probably worthwhile to spend some lines outlining our perception of the history of this subject (see also the recent review paper by Cardy [10]): It has been recognized by physicists some decades ago that two-dimensional systems from statistical physics near their critical temperatures have some universal features. In particular, some quantities (correlation length for instance) obey universal power laws near the critical temperature, and the value of the (critical) exponent in fact depends only on the phenomenological features of the discrete system (for instance, it is the same for the same model, taken on different lattices).…”
Section: Introductionmentioning
confidence: 99%
“…It is not clear to me what 2D results translate into four dimensions because the phase space in two dimensions is so constrained. But there are certainly consequences for condensed matter physics, where conformal structures do exist (see, for example, [11]). (ii) The connection between operator scaling dimension in a CFT and missing energy distributions was made for ordinary particles with integral scaling dimension in [12].…”
Section: 221601 (2007) P H Y S I C a L R E V I E W L E T T E R S mentioning
confidence: 99%
“…Under some symmetry conditions on T , Russo-Seymour-Welsh theory ensures that at criticality, the probability of C δ (Ω, A, B, C, D) is bounded away from both 0 and 1 as δ goes to 0. Its limit was conjectured by Cardy (see [6]) using non-rigorous arguments from conformal field theory; actual convergence was proved, in the case of the triangular lattice (embedded in such a way that its faces are equilateral triangles), by Smirnov (see [15,3]). We defer the statement of the convergence to a later time.…”
Section: The Probabilistic Modelmentioning
confidence: 99%